AKT/GSK3β‐Dependent Autophagy Contributes to the Neuroprotection of Limb Remote Ischemic Postconditioning in the Transient Cerebral Ischemic Rat Model - Qi, Zhi‐Feng (CNS Neurosci Ther, 2012)
BACKGROUND: Limb remote ischemic postconditioning (RIPostC) has been recognized as an applicable strategy in protecting against cerebral ischemic injury. However, the time window for application of limb RIPostC and the mechanisms behind RIPostC are still unclear. AIMS: In this study, we investigated the protective efficacy and the role of autophagy in limb RIPostC using a transient middle cerebral artery occlusion rat model. RESULTS: Limb RIPostC applied in the early phase of reperfusion reduced infarct size and improved neurological function. Autophagy levels in penumbral tissues were elevated in neurons of limb RIPostC rats, with an increase in the phosphorylation of AKT and glycogen synthase kinase 3β (GSK3β). Blocking the AKT/GSK3β pathway via the AKT inhibitor LY294002 prior to limb RIPostC suppressed the RIPostC‐induced autophagy and resulted in the activation of caspase‐3 in RIPostC rats, suggesting a critical role for AKT/GSK3β‐dependent autophagy in reducing cell death after cerebral ischemia. CONCLUSIONS: These results aid optimization of the time window for RIPostC use and offer novel insight into, and a better understanding of, the protective mechanism of autophagy in limb RIPostC.